Central serous chorioretinopathy following an episode of angioedema: An interesting case report (Indian Journal of Case Reports, 2021)
Central serous chorioretinopathy (CSCR) is a common disease of the middle-aged population with largely unknown etiology. We report the case of CSCR in a 37-year-old patient following an episode of angioedema who presented with sudden diminution of vision in the left eye 2 days following an episode of angioedema, which had been managed with a short course of steroids and antihistamines. On evaluation, he was found to have subretinal fluid at the macula in the affected eye, suggestive of CSCR. The patient was conservatively managed. The patient had recovery of symptoms with conservative management over a long period. The association of angioedema and its treatment as an underlying cause of CSCR needs to be explored. To the best of our knowledge, this is the first such case to be reported worldwide.